Ichthyofauna in Keliling and Pangelang Protected Lakes in Kapuas Hulu Regency - Sri Endah Purnamaningtyas (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Ichthyological diversity of the Pangelang and Keliling protected lakes are scarce. The study aimed to analyze the diver-sity of fish species in both lacustrine ecosystems. Sample collection was made by stratification sampling method in the core, buffer and free zones of lakes. All samples obtained by using fishing gears such as traps, gill nets and seine nets. The study successfully collected and identified 30 species (11 families) from the Lake Keliling and 21 species (9 fami-lies) from the Lake Pangelang. The most dominant species found in the Lake Keliling was Pseudeutropius brachypo-pterus (52.08%), and followed by Helostoma temminkii (29.53%). The dominance of species in Lake Pangelang was Thynnichthys polylepis (44.55%), and followed by Helostoma temminckii (15.17%). Abstrak Data iktiofauna ikan Danau Lindung Pangelang dan Keliling masih sangat minim. Penelitian ini bertujuan untuk meng-analisis keanekaragaman jenis ikan di kedua ekosistem lakustrin tersebut. Koleksi sampel dilakukan dengan stratifikasi sampling, di zona inti, zona penyangga, dan zona bebas. Sampel didapatkan dengan menggunakan alat tangkap seperti bubu dan jaring insang dan jala. Penelitian berhasil mengoleksi dan mengidentifikasi 30 spesies (11 famili) ikan dari Danau Lindung Keliling dan 21 spesies (9 famili) dari Danau Lindung Pangelang. Spesies yang paling dominan dite-mukan di Danau Lindung Keliling adalah Pseudeutropius brachypopterus (52,08%), disusul Helostoma temminkii (29,53%), sedangkan dominansi spesies di Danau Lindung Pangelang adalah Thynnichthys polylepis (44,55%), disusul Helostoma temminckii (15,17%).